Avoidant Attachment pada Mahasiswa: Disfungsi Peran Sosial dalam Relasi Interpersonal di Lingkungan Kampus - Salsa Nuzhlul Azzura; Siti Komariah; Puspita Wulandari (Indo Publishing, 2026)
Avoidant Attachment is an attachment pattern characterized by an individual’s tendency to withdraw from emotional closeness and avoid interpersonal dependency. This study aims to analyze how avoidant attachment among university student contributes to social role dysfunction in interpersonal relationship within the campus environment, through a sociological perspective. The study employs a qualitative approach combining literature review and semi-structured interview with one active student at Universitas Pendidikan Indonesia (UPI). Analysis was conducted using three theoretical frameworks, Talcott Parsons’ structural functionalism to examine failures in social role integration, Robert K.Merton’s strain theory to understand retreatism as an adaptive response to relational pressure, and Erving Goffman’s dramaturgy theory to explore impression management as a self-protective strategy. The findings indicate that student with avoidant attachment tend to engage in social withdrawal, avoid conflict resolution, an defensively manage self presentation, resulting in the deterioration of peer interpersonal relationships. Family background was identified as a primary socialization factor shaping these behavioral patterns. This study affirms that avoidant attachment is not merely an individual psychological matter, but a social phenomenon affective the integrative function of campus interaction systems.